2012
DOI: 10.1017/s0022215112001971
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of focal adhesion kinase in cellular proliferation, apoptosis and prognosis of laryngeal squamous cell carcinoma

Abstract: These findings suggest that focal adhesion kinase may affect laryngeal squamous cell carcinoma progression through regulation of cell apoptosis and proliferation. Focal adhesion kinase expression is a major prognostic factor in laryngeal cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The mean percentage of patients with advanced stages of disease was 52.0% (range, 0–100%). Five studies evaluated hepatocellular carcinoma [ 34 , 35 , 39 , 46 , 56 ], Four studies each evaluated gastric cancer [ 10 , 33 , 37 , 47 ] and ovarian cancer [ 36 , 41 , 49 , 58 ], three studies each evaluated lung cancer [ 40 , 45 , 55 ], and colorectal cancer[ 52 – 54 ], two studies each evaluated pancreatic cancer [ 15 , 44 ], and cholangiocarcinoma [ 38 , 42 ], and one study each evaluated breast cancer [ 48 ], gliomas [ 49 ], endometrial carcinoma [ 32 ], esophageal squamous cell carcinoma [ 16 ], renal cancer [ 51 ], tongue squamous cell carcinoma [ 50 ], and laryngeal squamous cell carcinoma [ 57 ]. Twenty studies were performed in Asian populations, while the remaining 10 studies were conducted in Western populations.…”
Section: Resultsmentioning
confidence: 99%
“…The mean percentage of patients with advanced stages of disease was 52.0% (range, 0–100%). Five studies evaluated hepatocellular carcinoma [ 34 , 35 , 39 , 46 , 56 ], Four studies each evaluated gastric cancer [ 10 , 33 , 37 , 47 ] and ovarian cancer [ 36 , 41 , 49 , 58 ], three studies each evaluated lung cancer [ 40 , 45 , 55 ], and colorectal cancer[ 52 – 54 ], two studies each evaluated pancreatic cancer [ 15 , 44 ], and cholangiocarcinoma [ 38 , 42 ], and one study each evaluated breast cancer [ 48 ], gliomas [ 49 ], endometrial carcinoma [ 32 ], esophageal squamous cell carcinoma [ 16 ], renal cancer [ 51 ], tongue squamous cell carcinoma [ 50 ], and laryngeal squamous cell carcinoma [ 57 ]. Twenty studies were performed in Asian populations, while the remaining 10 studies were conducted in Western populations.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al demonstrated that Akt promotes cell survival through its ability to phosphorylate and activate several pro-apoptotic targets. Subsequent consequences of this include the phosphorylation of Fak and the activation of signal transduction pathways, ultimately contributing to AURKA-mediated tumorigenesis (31). However, the pathway by which the migration and invasion of HNSCC was enhanced was not determined.…”
Section: Discussionmentioning
confidence: 99%